CULTURAL COMMUNICATION PERSPECTIVE ON EDUCATIONAL TRANSFORMATION: A CRITICAL STUDY BASED ON REPRESENTATION THEORY STUART HALL - Jufriyanto, Jufriyanto; Jauhari, Minan; Wazis, Kun (FORUM PAEDAGOGIK, 2025)
Education in the era of globalization requires a renewed understanding of how culture and identity are represented within learning spaces. This study examines cultural communication in education through Stuart Hall’s theoretical framework, particularly his theory of representation and the encoding/decoding model. The research employs a qualitative approach using library research, focusing on Hall’s works and contemporary literature on multicultural education. The findings indicate that education functions as a symbolic space where ideologies and identities are constructed. Indonesia’s education system remains biased toward dominant cultural values while marginalizing minority narratives. An inclusive and adaptive communication model is necessary to foster culturally equitable educational practices.